Potential health effects of locally-manufactured corn-mill grinding plates (Journal of Science and Technology, 2016)
Laboratory tests were carried out on samples of some locally-manufactured corn-mill grinding plates to investigate the possible causes of their early wear and failure. Three different samples selected from the same local manufacturer were tested for chemical composition and micro-structural, as well as wear and hardness. Results show that, although the chemical compositions were similar, the hardness and wear resistance of samples were significantly different, suggesting that the samples were of different heats. A strong correlation exists between the wear rate and micro-hardness of samples, the wear rate decreasing linearly with hardness. Since the grinding/milling plates were from the same production shop and meant for the same purpose, these differences in hardness and wear resistance indicates non-reproducibility of products. The differences in hardness and wear resistance of the samples are explained in terms of chemical composition and/or microstructures of samples. The wear of these locally-manufactured corn-mill grinding/milling plates is discussed in terms of the possibility of consumption of iron into the human body and the health hazards associated with it.